The Routledge handbook on contemporary Turkey
1 online resource (xvii, 516 pages)
Keywords: "This Handbook discusses the new political and social realities in Turkey from a range of perspectives, both emphasizing change as well as continuities. Contextualizing recent developments, the chapters, written by experts in their fields, combine analytical depth with a broad overview. In the last few years alone, Turkey has experienced a failed coup attempt, a prolonged state of emergency, the development of a presidential system based on the supreme power of the head of state, a crackdown on traditional and new media, universities and civil society organisations, the detention of journalists, mayors, members of parliament, establishment of political tutelage over the judiciary and a staggering economic crisis. It also terminated talks with the Kurdistan Workers Party PKK, intervened and occupied mountainous border areas in Northern Iraq to fight the organization, occupied Afrin and strips of territory in Northern Syria, intervened in Libya, articulated an assertive transnational politics towards 'kin' across the world, and strained its relations with the EU and the US, while developing relations with Russia, flirting with China's intercontinental Belt and Road Initiative, and carving out a presence in Africa, to name just a few of the most recent developments. This volume provides a comprehensive and wide-ranging overview of the making of modern Turkey. It is a key reference for students and scholars interested in political economy, security studies, international relations and Turkish studies"--